PENERAPAN MODEL PEMBELAJARAN INKUIRI DALAM MENINGKATKAN PEMAHAMAN MAHASISWA PADA MATA KULIAH BIOESKPERIMENTAL - Ervina Mukharomah; Saleh Hidayat (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research is a quantitative study of disasters making descriptions, pictures or paintings systematically, factually and accurately regarding the facts, characteristics and relationships between the phenomena being studied. The purpose of this study was to determine the understanding ability of students in the bioexperimental subject. Based on the research that has been done it can show that the free inquiry learning model (Free Inqury) is suitable to be applied to the Bioexperimental subject. The final score of students in the bio-experimental courses that completed in the 2016/2017 academic year was 44% and in the experimental class the completeness score was 90%. With the meaning that student understanding increases with the application of the free inquiry learning model.